Penggunaan Metode AHE (Anak Hebat) dalam Meningkatkan Literasi Anak Usia Dini: Tantangan dan Potensi - Maisyarah Maisyarah; Desi Ismawati; Jamilah Jamilah; Mira Sri Rastiti (ABATATSA: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to gain a deeper understanding of the efforts to improve reading and writing abilities in early childhood at the AHE institution. The researcher seeks to identify the challenges faced in achieving this goal, as well as the potential opportunities that can be utilized. Through direct classroom observations, interviews with teachers and parents, and analysis of related documents, the researcher endeavors to obtain a comprehensive overview. The results of this research indicate that there are several challenges, such as a lack of teacher training and limited time for literacy activities. However, on the other hand, there is significant potential to enhance children's literacy. For example, by utilizing the surrounding environment as a learning medium, actively involving parents, and employing appropriate technology. Overall, this research concludes that improving early childhood literacy at AHE requires a concerted effort from various parties. By addressing the existing challenges and capitalizing on available opportunities, it is hoped that children at AHE can grow into active and independent readers.